Antioxidant Activity of Sunflower (Helianthus Annuus l.) Ethanolic Extract with DPPH Method and Determination of Total Phenolic and Flavonoid Levels - Salwa Salwa (Universitas Muhammadiyah Surakarta, 2021)
Sunflower (Helianthus annuus L.) is believed to have antioxidant properties. Currently, there are many studies examining compounds that have benefits as antioxidants and are safe for health. However, the sunflower only examined the antioxidants in sunflower seeds. This study aims to determine the antioxidant activity of ethanol extract of flowers, bark, and leaves of sunflowers. The antioxidant activity test using the DPPH method showed the highest antioxidant activity was found in the leaf extract (Helianthus annuus L.) with an IC50 value of 48.841 ppm. The highest phenolic content was found in leaf samples with a value of 35.149 mg gallic acid equivalent/gram extract and the highest determination of flavonoid levels was found in leaf samples with a value of 10.917 mg quercetin equivalent/gram extract.